Ni-based catalyst supported on mesostructured silica nanoparticles (MSN) for methanol oxidation reaction (MOR) - Muliani Mansor; Sharifah Najiha Timmiati; Lim, Kean Long; Azran Mohd Zainoodin; Nurul Hidayatul Nazirah Kamarudin (Penerbit Universiti Kebangsaan Malaysia, 2018)
A new catalyst based on mesostructured silica nanoparticle (5wt%, 20wt%, and 30wt% Ni-MSN) were prepared by the wet impregnation method and used for electro-oxidation of methanol. While, MSN as a catalyst support was synthesized using co-condensation and sol-gel method. The synthesized MSN and Ni-MSN were characterized using X-ray diffraction (XRD), field emission scanning electron microscopy (FESEM), and Fourier Transform Infra-red (FTIR) techniques. Ni-MSN catalysts were successfully prepared by mixing with the conducting graphite in 1:1 ratio which called carbon paste electrode (CPE). Mixing with graphite, in this work, was particular necessary to increase the electrical conductivity of the Ni-MSN materials. For fuel cell applications, the electrochemical measurements for methanol oxidation were investigated using cyclic voltammetry (CV) and chronoamperometry (CA) in 1.0 M NaOH and 1.0 M CH3 OH for modified electrode, Ni-MSNCPE. Among the three samples, 30wt% Ni-MSNCPE exhibits a high current density (~ 8 mA cm-2) and long-term chronoamperometry stability (3600 s) toward methanol oxidation in alkaline solution. This may attribute to the high dispersion of nickel and ordered mesoporous structure which can facilitate the diffusion of methanol and products. 30wt% Ni nanoparticles supported onto MSN catalyst demonstrate better electrocatalytic activity and stability than the 5wt% and 20wt% Ni-MSNCPE catalysts.